Low-temperature non-shrinkage grouting material, and preparation method and construction method thereof
Patent Information
- Application Number
- CN202611136243.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-09-29
AI Technical Summary
[0005]本发明旨在提供一种低温无收缩注浆材料、及其制备方法和施工方法,以解决或改善上述技术问题中现有注浆材料难以同时满足低温快速固化、固化无收缩、长期防渗耐久以及复杂土层适配施工的问题
通过采用分别预制的硅溶胶基液相组分、低温固化活性固相组分和复合活化调凝组分,并使三者在施工前混合形成可泵送注浆浆液,能够避免液相材料与固相活性材料在储存阶段提前发生水化、絮凝或凝胶反应,提高材料储存稳定和现场施工适配。
Smart Images

Figure CN122831653A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of geotechnical grouting materials, and more specifically, to a low-temperature non-shrink grouting material, its preparation method, and its construction method. Background Technology
[0002] In geotechnical engineering foundation reinforcement, seepage prevention and plugging construction, cement-based, silica sol-based or composite chemical grouting materials are often used to grout soft soil foundations, deep foundation pit water-stop curtains, tunnel surrounding rock and dams.
[0003] Cement-based grouting materials are low in cost and high in strength, but their coarse particles limit their permeability and impermeability, and they are prone to shrinkage during curing. Silica sol-based grouting materials have some permeability, but they usually rely on sodium silicate and acidic modifiers, resulting in high cost, strong corrosivity, and insufficient environmental friendliness. Composite chemical grouting materials can improve some properties, but their gel time and curing effect are greatly affected by temperature, moisture content, and soil pore structure. Especially in low-temperature environments below 5°C, existing grouting materials generally suffer from insufficient curing activity, slow setting and hardening, easy formation of micro-cracks after curing, and poor impermeability durability.
[0004] To address these issues, a low-temperature non-shrink grouting material, its preparation method, and its construction method are proposed. Summary of the Invention
[0005] The present invention aims to provide a low-temperature non-shrink grouting material, its preparation method and construction method, in order to solve or improve the problem that existing grouting materials are unable to simultaneously meet the requirements of low-temperature rapid curing, non-shrink curing, long-term impermeability and durability, and adaptability to complex soil layers.
[0006] In view of this, a first aspect of the present invention is to provide a low-temperature non-shrink grouting material.
[0007] A second aspect of the present invention is to provide a preparation method.
[0008] A third aspect of the present invention is to provide a construction method.
[0009] The first aspect of this invention provides a low-temperature non-shrink grouting material, comprising pre-prepared silica sol-based liquid phase components, low-temperature curing active solid phase components, and composite activated and regulating setting components; by mass parts, the silica sol-based liquid phase component comprises 45-52 parts, the low-temperature curing active solid phase component comprises 35-42 parts, and the composite activated and regulating setting component comprises 8-13 parts; the silica sol-based liquid phase component is a neutral, low-viscosity modified silica sol liquid phase, and includes 28-34 parts modified silica sol, 10-15 parts deionized water, 2.5-3.8 parts nano-titanium dioxide dispersion, 0.8-1.5 parts organic retarding dispersant, and 0.2-0.5 parts environmentally friendly chelating agent; the low-temperature... The solidified active solid phase component is a low-temperature solidified active solid phase, comprising 18-22 parts of ultrafine slag powder, 7-10 parts of high-alumina cement, 5-7 parts of calcined kaolin, 2.5-4 parts of expanded microspheres, 2-3.5 parts of basalt ultrafine powder, and 0.5-1.2 parts of water-soluble starch ether; the composite activated setting-regulating component is an activated regulating phase, comprising 3.5-5 parts of anhydrous sodium sulfate, 1.2-2.5 parts of trisodium citrate, 2-3.5 parts of nano-calcium carbonate, and 0.8-1.5 parts of polyethylene glycol; wherein, the silica sol-based liquid phase component, the low-temperature solidified active solid phase component, and the composite activated setting-regulating component are mixed to form a pumpable grouting slurry with a total solid content of 38-45 wt%.
[0010] A second aspect of the present invention provides a preparation method comprising the following steps: sequentially mixing deionized water, modified silica sol, nano-titanium dioxide dispersion, organic retarding dispersant, and environmentally friendly chelating agent, and obtaining a silica sol-based liquid phase component after filtration; grinding and mixing ultrafine slag powder, high-alumina cement, calcined kaolin, and basalt ultrafine powder, adding expanded microspheres and water-soluble starch ether for mixing, and obtaining a low-temperature curing active solid phase component after sieving; mixing anhydrous sodium sulfate, trisodium citrate, and nano-calcium carbonate, adding polyethylene glycol for further mixing, and obtaining a composite activated setting-regulating component after sieving; sealing and storing the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component separately, and mixing them according to a preset ratio to form a grouting slurry before construction.
[0011] A third aspect of the present invention provides a construction method comprising the following steps: determining the moisture content, porosity, particle size distribution, groundwater level, and ambient temperature of the soil layer to be grouted, and determining the mixing ratio of the silica sol-based liquid phase component, the low-temperature solidification active solid phase component, and the composite activated setting-regulating component based on the determination results; mixing the silica sol-based liquid phase component, the low-temperature solidification active solid phase component, and the composite activated setting-regulating component according to the mixing ratio to prepare a grouting slurry; drilling grouting holes in the area to be grouted, and lowering a vibratory grouting pipe to the target grouting depth within the grouting holes; starting the grouting equipment and the vibratory grouting pipe, allowing the grouting slurry to enter the pores of the soil layer to be grouted under grouting pressure and vibration; after completing the bottom grouting, raising the vibratory grouting pipe layer by layer according to a preset lifting height, and increasing the grouting pressure and vibration frequency layer by layer during the raising process, so that the grouting slurry diffuses along soil layers of different depths; and after grouting to the preset height, stabilizing and sealing the hole, and allowing the grouting slurry to solidify in the soil layer to form an impermeable reinforced body.
[0012] The beneficial effects of this invention compared to the prior art are as follows: By using pre-prepared silica sol-based liquid phase components, low-temperature curing active solid phase components, and composite activated setting-regulating components, and mixing the three before construction to form a pumpable grout, it is possible to avoid premature hydration, flocculation, or gelation reactions between the liquid phase materials and the solid active materials during the storage stage, thereby improving the material storage stability and on-site construction compatibility.
[0013] Through the synergistic effect of modified silica sol, nano-titanium dioxide dispersion, organic retarder dispersant and environmentally friendly chelating agent in the silica sol-based liquid phase component, the slurry can maintain a low viscosity and good dispersion stability, thereby improving the slurry's ability to penetrate into soft soil foundations, surrounding rock fissures and the fine pores of the seepage prevention curtain.
[0014] By using ultrafine slag powder, high-alumina cement, calcined kaolin, and ultrafine basalt powder in the low-temperature curing active solid phase component to form a cementitious active skeleton, the hydration and curing ability of the grout in a low-temperature environment can be improved, so that the grout can still solidify and harden relatively quickly below 5°C, thereby improving the problem of insufficient low-temperature curing activity of existing grouting materials and limited construction in winter.
[0015] By synergistically regulating the low-temperature activation reaction and gelation process using anhydrous sodium sulfate, trisodium citrate, nano-calcium carbonate, and polyethylene glycol in the composite activation and setting-regulating components, the gelation time of the grout can be controlled while ensuring low-temperature curing efficiency. This reduces the problems of pipe blockage caused by excessively rapid gelation or uncontrolled diffusion caused by excessively slow gelation, thereby improving the controllability of the grouting construction process.
[0016] By introducing expanded microspheres into the low-temperature curing active solid phase component, and combining them with micro-fillers such as nano-titanium dioxide, nano-calcium carbonate, and ultrafine basalt powder, the volume shrinkage of the cementitious system can be compensated during the curing process, and the internal pore connectivity of the cured body can be reduced, thus reducing the generation of microcracks and improving the volume stability, impermeability, and long-term durability of the cured body.
[0017] Additional aspects and advantages of embodiments of the invention will become apparent in the following description or may be learned by practice of embodiments of the invention. Attached Figure Description
[0018] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This is a schematic diagram of the preparation method of the low-temperature non-shrink grouting material of the present invention; Figure 2 This is a schematic diagram of the construction method for the low-temperature non-shrink grouting material of the present invention. Detailed Implementation
[0019] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.
[0020] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0021] Please see Figures 1-2 The following describes a low-temperature non-shrink grouting material according to some embodiments of the present invention, as well as its preparation method and construction method.
[0022] An embodiment of the first aspect of the present invention provides a low-temperature non-shrink grouting material. In some embodiments of the present invention, the low-temperature non-shrink grouting material comprises pre-prepared silica sol-based liquid phase components, low-temperature curing active solid phase components, and composite activated setting-regulating components; by mass parts, the silica sol-based liquid phase component is 45-52 parts, the low-temperature curing active solid phase component is 35-42 parts, and the composite activated setting-regulating component is 8-13 parts.
[0023] The silica sol-based liquid phase component is a neutral, low-viscosity modified silica sol liquid phase, which, by mass parts, includes 28-34 parts of modified silica sol, 10-15 parts of deionized water, 2.5-3.8 parts of nano-titanium dioxide dispersion, 0.8-1.5 parts of organic retarding dispersant, and 0.2-0.5 parts of environmentally friendly chelating agent.
[0024] The low-temperature curing active solid phase component comprises, by mass parts, 18-22 parts of ultrafine slag powder, 7-10 parts of high-alumina cement, 5-7 parts of calcined kaolin, 2.5-4 parts of expanded microspheres, 2-3.5 parts of basalt ultrafine powder, and 0.5-1.2 parts of water-soluble starch ether.
[0025] The composite activated condensation regulating component is an activated regulating phase, which, by mass parts, includes 3.5 to 5 parts of anhydrous sodium sulfate, 1.2 to 2.5 parts of trisodium citrate, 2 to 3.5 parts of nano-calcium carbonate, and 0.8 to 1.5 parts of polyethylene glycol.
[0026] The mixture of silica sol-based liquid phase component, low-temperature curing active solid phase component and composite activated setting-regulating component forms a pumpable grout with a total solid content of 38-45 wt%.
[0027] The present invention provides a low-temperature non-shrink grouting material, which is configured as a pre-made silica sol-based liquid phase component, a low-temperature curing active solid phase component, and a composite activated setting-regulating component, instead of pre-mixing all raw materials into a single component. This is to avoid premature hydration, flocculation, or gelation reactions between the liquid phase silica sol and the solid phase cementitious material during the storage stage, so that each component can remain stable before construction and be mixed on-site according to the grouting conditions to form a pumpable grout.
[0028] The silica sol-based liquid phase component uses a neutral, low-viscosity modified silica sol liquid phase as the main component. The modified silica sol forms a continuous nano-silicon network structure in the slurry and interacts with the low-temperature curing active solid phase component during the curing process. Deionized water is used to adjust the fluidity and dispersion stability of the liquid phase system, reducing the impact of impurity ions on the stability of the silica sol. Nano-titanium dioxide dispersion fills the micropores in the cured body and improves its durability. Organic retarding dispersants improve the dispersion state of nanoparticles and gel particles, preventing premature coagulation of the slurry before pumping. Environmentally friendly chelating agents complex trace metal ions in the system, reducing the interference of impurity ions on gel time and slurry stability.
[0029] The low-temperature curing active solid components primarily utilize ultrafine slag powder, high-alumina cement, and calcined kaolin as sources of cementitious activity. Ultrafine slag powder provides potential hydraulic activity and participates in the formation of calcium silicate hydration products; high-alumina cement provides rapid early hydration reactions at low temperatures; and calcined kaolin enhances the pozzolanic reactivity of the system. Together, these three components improve the material's setting and hardening capacity under low-temperature conditions. Expanded microspheres provide micro-expansion compensation and lightweight filling during curing to offset volume changes caused by hydration shrinkage and drying shrinkage of the cementitious system, reducing the formation of microcracks after curing. Ultrafine basalt powder acts as an inert or weakly active microfiller to fill interparticle gaps, improving the density and compressive strength of the solidified skeleton. Water-soluble starch ether improves the water retention and anti-segregation properties of the slurry, ensuring uniform suspension of solid particles in the liquid phase and reducing the risk of sedimentation and bleeding.
[0030] The composite activated setting regulator is used to adjust the low-temperature curing reaction and gel time. Among them, anhydrous sodium sulfate can activate the hydration activity of ultrafine slag powder and high-alumina cement, so that the cementitious system can maintain a high reaction rate at low temperature of 0-5℃. Trisodium citrate can regulate the gel time, avoiding pipe blockage caused by excessively rapid slurry setting, and also avoiding uncontrolled slurry diffusion caused by excessively slow gelation. Nano-calcium carbonate can act as a crystal nucleus and microfiller material, promoting the nucleation and growth of hydration products and filling micropores. Polyethylene glycol can improve the wettability and dispersibility of powder, so that the activated setting regulator can be quickly and uniformly distributed during the mixing process. This allows the composite activated setting regulator to maintain low-temperature curing activity and keep the slurry at a suitable working time and gel time.
[0031] By limiting the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activation and setting-regulating component to the aforementioned mass fraction range, a balance can be achieved between the slurry's fluidity, gelation rate, early strength, later strength, and volumetric stability. If the silica sol-based liquid phase component is too small, the slurry's fluidity decreases, hindering its penetration into fine pores; if it is too large, the solid-phase gelation framework is insufficient, potentially reducing the strength of the cured body. If the low-temperature curing active solid phase component is too small, the low-temperature curing strength is insufficient; if it is too large, the slurry viscosity increases, increasing pumping resistance. If the composite activation and setting-regulating component is too small, the low-temperature activation and gelation control effects are insufficient; if it is too large, it may lead to excessively rapid gelation or decreased system stability. This ensures rapid curing of the material under low-temperature conditions, forming a cured body with low shrinkage, high density, and high impermeability.
[0032] The three components, when mixed, form a pumpable grout with a total solids content of 38–45 wt%. This range of total solids content balances the fluidity required for grouting construction and the structural strength required after curing. When the total solids content is low, although the grout has good fluidity, the solidified body skeleton material is insufficient, which can easily affect the compressive strength and impermeability. When the total solids content is high, the viscosity of the grout increases, which can easily cause pumping difficulties or insufficient grout diffusion radius. Controlling the total solids content at 38–45 wt% enables the grout to maintain good pumpability, pore penetration capacity, and curing effect in scenarios such as soft soil foundations, deep foundation pit cutoff walls, tunnel surrounding rock, and dam seepage prevention.
[0033] Specifically, the modified silica sol is a neutral hydroxyl-modified silica sol; the neutral hydroxyl-modified silica sol has a particle size of 12-18 nm, a silica solid content of 32-38 wt%, a pH value of 6.8-7.5, a viscosity of 1.2-1.8 mPa·s, and a surface hydroxyl grafting rate of 12-15%.
[0034] In the embodiments provided by the present invention, the modified silica sol can be a neutral hydroxyl-modified silica sol, the particle size of which can be 12nm, 15nm or 18nm, the silica solid content can be 32wt%, 35wt% or 38wt%, the pH value can be 6.8, 7.2 or 7.5, the viscosity can be 1.2mPa·s, 1.5mPa·s or 1.8mPa·s, and the surface hydroxyl grafting rate can be 12%, 13.5% or 15%.
[0035] By using the above-mentioned neutral hydroxyl-modified silica sol, the silica sol-based liquid phase components can maintain low viscosity and stable dispersion under near-neutral conditions, avoiding the adverse effects of strong acid, strong alkali, or high salt environments on grout stability, construction equipment, and groundwater environment. Furthermore, the hydroxyl groups on the surface of the neutral hydroxyl-modified silica sol can serve as interfacial active sites, forming interfacial bonds with low-temperature curing active solid phase components such as ultrafine slag powder, high-alumina cement, and calcined kaolin during the curing process of the grouting material. Together with the calcium silicate gel and aluminate hydration products formed by the hydration reaction, they form a continuous and dense cementitious skeleton.
[0036] Neutral hydroxyl-modified silica sol with particle sizes of 12nm, 15nm, or 18nm can penetrate well into the micropores and fissures of the soil layer. A silica solid content of 32wt%, 35wt%, or 38wt% can provide a source of silica network while ensuring the fluidity of the grout. A pH value of 6.8, 7.2, or 7.5 can improve the environmental compatibility and storage stability of the material system. A viscosity of 1.2mPa·s, 1.5mPa·s, or 1.8mPa·s can reduce the pumping resistance of the grout and expand the grouting diffusion range. A surface hydroxyl grafting rate of 12%, 13.5%, or 15% can enhance the bonding strength between the liquid phase component and the solid phase cementitious material while avoiding premature flocculation of the system.
[0037] Specifically, the nano-titanium dioxide dispersion has a particle size of 5-8 nm, a solid content of 20-25 wt%, and a rutile crystal form; the dispersion medium of the nano-titanium dioxide dispersion is deionized water.
[0038] In the embodiments provided by the present invention, the nano-titanium dioxide particle size in the nano-titanium dioxide dispersion can be 5nm, 6.5nm or 8nm, the solid content can be 20wt%, 23wt% or 25wt%, the crystal form is rutile, and the dispersion medium is deionized water.
[0039] By using the above-mentioned nano-titanium dioxide dispersion, the fine filling effect of nano-titanium dioxide particles can be utilized to enter the micropores of the gel skeleton formed by the silica sol-based liquid phase component and the low-temperature curing active solid phase component, thereby reducing the internal pore connectivity of the cured body.
[0040] Nano-titanium dioxide with particle sizes of 5nm, 6.5nm, or 8nm is beneficial for uniform dispersion and filling of micropores in slurry. Solid content of 20wt%, 23wt%, or 25wt% can provide sufficient inorganic nano-filler phase without significantly increasing slurry viscosity. The dispersion medium is deionized water, which can reduce the interference of impurity ions on the stability of silica sol, gel time, and low-temperature curing reaction, so that the nano-titanium dioxide dispersion has good compatibility with silica sol-based liquid phase components.
[0041] Specifically, the specific surface area of the ultrafine slag powder is 480-520 m² / kg and the activity index is not less than 95%; the low-temperature hydration activity of high-alumina cement at 0℃ is greater than 0.6; the particle size of calcined kaolin is not greater than 5 μm; and the particle size of basalt ultrafine powder is not greater than 10 μm.
[0042] In the embodiments provided by the present invention, the specific surface area of the ultrafine slag powder can be 480m² / kg, 500m² / kg or 520m² / kg, and the activity index can be 95%, 98% or 102%; the low-temperature hydration activity of high-alumina cement at 0℃ can be 0.62, 0.68 or 0.75; the particle size of calcined kaolin can be 3μm, 4μm or 5μm; and the particle size of basalt ultrafine powder can be 6μm, 8μm or 10μm.
[0043] By employing the aforementioned ultrafine slag powder, high-alumina cement, calcined kaolin, and basalt ultrafine powder, it is possible to achieve low-temperature solidification of active solid components, which possess low-temperature hydration reaction capability, pozzolanic reactivity, and micro-filling and reinforcing capabilities. Among these, the high specific surface area and activity index of the ultrafine slag powder facilitate its rapid participation in the hydration reaction under the action of the composite activated setting-regulating components, forming calcium silicate gel and improving the later-stage strength of the solidified body. High-alumina cement still exhibits high low-temperature hydration activity at 0℃, providing an early-stage cementitious skeleton and mitigating the problem of slow setting and hardening under low-temperature conditions. The fine particles of calcined kaolin can participate in secondary reactions and fill the pores between cementitious products.
[0044] Specifically, the expanded microspheres are hollow glass microspheres; The expanded microspheres have a particle size of 100–150 μm, a wall thickness of 10–15 μm, a bulk density of 0.25–0.35 g / cm³, and a volume expansion rate of 3–5%.
[0045] In the embodiments provided by the present invention, the expanded microspheres are hollow glass microspheres. The particle size of the expanded microspheres can be 100μm, 125μm or 150μm, the wall thickness can be 10μm, 12μm or 15μm, the bulk density can be 0.25g / cm³, 0.30g / cm³ or 0.35g / cm³, and the volume expansion rate can be 3%, 4% or 5%.
[0046] By employing the aforementioned hollow glass microspheres, their hollow and lightweight structure can form a micro-filling and skeletal support effect in the low-temperature curing active solid phase component, improving the gradation relationship between solid particles and reducing the internal pore connectivity of the slurry after curing. Furthermore, the hollow glass microspheres can provide a certain volume compensation effect during the curing process to offset the shrinkage deformation generated during the hydration and hardening of cementitious materials such as ultrafine slag powder, high-alumina cement, and calcined kaolin, thereby reducing the formation of microcracks inside the cured body.
[0047] Expanded microspheres with particle sizes of 100μm, 125μm, or 150μm can form a stable filling phase while ensuring the pumpability of the slurry. Wall thicknesses of 10μm, 12μm, or 15μm enable the expanded microspheres to have both compressive strength and volume compensation capabilities. Bulk densities of 0.25g / cm³, 0.30g / cm³, or 0.35g / cm³ can reduce the overall density of the solid phase components and improve the suspension stability of the slurry. Volume expansion rates of 3%, 4%, or 5% can compensate for curing shrinkage without excessively disturbing the solidified structure.
[0048] Specifically, the ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component is adjusted according to the construction environment temperature, soil moisture content, and soil porosity.
[0049] When the ambient temperature during construction is 5–25℃, the soil moisture content is 15–25%, and the soil porosity is 30–40%, the mass ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component is (48–52): (36–40): (10–13).
[0050] When the ambient temperature during construction is 0-5℃ and the soil moisture content is no more than 30%, the mass ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting component is (46-50): (38-42): (10-13).
[0051] When the soil moisture content is greater than 25% and the soil porosity is greater than 40%, the mass ratio of the silica sol-based liquid phase component, the low-temperature solidification active solid phase component, and the composite activated setting component is (50-54): (33-37): (11-14).
[0052] In the embodiments provided by the present invention, the ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component can be adjusted according to the construction environment temperature, soil moisture content, and soil porosity.
[0053] When the ambient temperature during construction is 5℃, 15℃, or 25℃, the soil moisture content is 15%, 20%, or 25%, and the soil porosity is 30%, 35%, or 40%, the mass ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component can be 48:36:10, 50:38:12, or 52:40:13, so that the grout can balance flow, gelation speed, and curing strength in conventional soil layers at room temperature.
[0054] When the ambient temperature during construction is 0℃, 3℃, or 5℃, and the soil moisture content is 22%, 26%, or 30%, the mass ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting regulating component can be 46:38:10, 48:40:12, or 50:42:13. By appropriately increasing the proportion of the low-temperature curing active solid phase component, the ultrafine slag powder, high-alumina cement, and calcined kaolin can maintain a high low-temperature hydration reaction capacity under the action of the composite activated setting regulating component, thereby improving the problem of slow setting and hardening under low-temperature conditions.
[0055] When the soil moisture content is 26%, 32%, or 38%, and the soil porosity is 41%, 45%, or 50%, the mass ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component can be 50:33:11, 52:35:13, or 54:37:14. By appropriately increasing the proportion of the silica sol-based liquid phase component and the composite activated setting-regulating component, the slurry can maintain good flow and diffusion capacity and gel regulation capacity in soil layers with high moisture content and large porosity, reducing insufficient diffusion caused by excessive slurry viscosity and attenuation of curing strength caused by high soil moisture content.
[0056] A second aspect of the present invention provides a method for preparing the low-temperature non-shrink grouting material in any of the above embodiments. In some embodiments of the present invention, such as... Figure 1 As shown, the preparation method includes the following steps: S101 involves sequentially mixing deionized water, modified silica sol, nano-titanium dioxide dispersion, organic retarding dispersant, and environmentally friendly chelating agent, followed by filtration to obtain a silica sol-based liquid phase component.
[0057] S102 involves grinding and mixing ultrafine slag powder, high-alumina cement, calcined kaolin, and ultrafine basalt powder, then adding expanded microspheres and water-soluble starch ether for further mixing. After sieving, a low-temperature solidified active solid phase component is obtained.
[0058] S103 is prepared by mixing anhydrous sodium sulfate, trisodium citrate, and nano-calcium carbonate, then adding polyethylene glycol and mixing further, followed by sieving to obtain a composite activated coagulation regulating component.
[0059] S104 involves sealing and storing the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component separately, and mixing them according to a preset ratio to form the grouting slurry before construction.
[0060] The present invention provides a preparation method in which a silica sol-based liquid phase component, a low-temperature curing active solid phase component, and a composite activated setting-regulating component are prepared and sealed for storage. This method avoids premature hydration, flocculation, or gelation reactions between the liquid phase material and the solid active material during storage, thereby improving the storage stability of each component. Before construction, the components are mixed according to a preset ratio to form a grouting slurry. This allows for flexible adjustment of the slurry properties based on the site temperature, soil moisture content, and porosity, resulting in a slurry with good pumpability, low-temperature curing activity, controllable gelation time, and volume stability after curing. This improves the adaptability of grouting construction and the seepage prevention and reinforcement effect.
[0061] In any of the above embodiments, the modified silica sol is prepared in the following manner: Tetraethyl orthosilicate and deionized water were mixed in a molar ratio of 1:8, ammonia was added as a catalyst, and the mixture was stirred and hydrolyzed at 40°C. After filtration and concentration, modified silica sol was obtained.
[0062] In any of the above embodiments, the step of separately sealing and storing the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component, and mixing them according to a preset ratio to form the grouting slurry before construction includes: Add agent A to the mixing container and stir at low speed. Add agent B in batches to agent A and stir to mix.
[0063] After agent B is evenly dispersed, agent C is added and stirring is continued. After stirring is completed, a grout with a viscosity of 350-450 mPa·s, a working time of 25-40 min, and a gel time of 15-35 min is obtained.
[0064] A third aspect of the present invention provides a construction method implemented using the low-temperature non-shrink grouting material described in any of the above embodiments. In some embodiments of the present invention, such as... Figure 2 As shown, the construction method includes the following steps: S201, determine the moisture content, porosity, particle size distribution, groundwater level and construction environment temperature of the soil layer to be grouted, and determine the mixing ratio of silica sol-based liquid phase component, low-temperature curing active solid phase component and composite activated setting regulating component based on the test results.
[0065] S202, the silica sol-based liquid phase component, the low-temperature curing active solid phase component and the composite activation and setting regulating component are mixed according to the mixing ratio to prepare the grouting slurry.
[0066] S203, Drill grouting holes in the area to be grouted, and lower the vibratory grouting pipe to the target grouting depth in the grouting holes.
[0067] S204, start the grouting equipment and vibrating grouting pipe to allow the grout to enter the pores of the soil layer to be grouted under the grouting pressure and vibration.
[0068] S205: After the bottom grouting is completed, the vibratory grouting pipe is raised layer by layer according to the preset lifting height, and the grouting pressure and vibration frequency are increased layer by layer during the lifting process so that the grouting slurry can spread along soil layers of different depths.
[0069] S206 involves stabilizing and sealing the grout after it has been injected to a preset height, and then allowing the grout to solidify in the soil layer to form a seepage-proof reinforced body.
[0070] This invention provides a construction method that, before construction, measures the moisture content, porosity, particle size distribution, groundwater level, and ambient temperature of the soil layer to be grouted, and determines the mixing ratio of the three components accordingly. This ensures that the fluidity, gel time, and curing strength of the grout match the site conditions. By lowering the vibratory grouting pipe to the target depth and coordinating grouting pressure and vibration during the grouting process, the grout can be uniformly diffused into the pores and fissures of the soil layer, improving grout fullness. By raising the vibratory grouting pipe in layers and gradually increasing the grouting pressure and vibration frequency, soil layers at different depths can be adequately filled with grout, reducing problems such as localized missed grouting, insufficient diffusion, or material waste. Finally, by stabilizing the pressure and sealing the borehole and solidifying in situ, a seepage-proof reinforced body is formed, which is beneficial for improving the foundation reinforcement effect and seepage-proof compaction.
[0071] To further illustrate the present invention, the following detailed description, in conjunction with specific embodiments, describes the low-temperature non-shrink grouting material, its preparation method, and its construction method provided by the present invention. The modified silica sol, nano-titanium dioxide dispersion, ultrafine slag powder, high-alumina cement, calcined kaolin, expanded microspheres, basalt ultrafine powder, anhydrous sodium sulfate, trisodium citrate, nano-calcium carbonate, polyethylene glycol, and other raw materials used in the following embodiments can all be commercially available products, or can be prepared or processed in advance according to the aforementioned method of the present invention. It should be noted that the following embodiments are only used to illustrate the technical solution of the present invention and do not constitute a limitation on the scope of protection of the present invention. Without departing from the technical concept of the present invention, those skilled in the art can adaptively adjust the distribution ratio and process parameters of each component according to the construction environment temperature, soil moisture content, soil porosity, and grouting construction requirements.
[0072] In the following embodiments, agent A is a silica sol-based liquid phase component, agent B is a low-temperature curing active solid phase component, and agent C is a composite activated and regulating component. In each embodiment, agents A, B, and C are prepared and sealed according to the aforementioned preparation method of the present invention. Before construction or testing, they are mixed according to the corresponding mass proportions to form a grouting slurry, and the slurry performance, curing strength, curing shrinkage rate, and impermeability are tested under corresponding environmental conditions.
[0073] Example 1 This embodiment provides a low-temperature, non-shrink grouting material, comprising 50 parts by weight of agent A, 38 parts by weight of agent B, and 12 parts by weight of agent C. The test environment temperature was 18°C, the moisture content of the soil layer to be grouted was 20%, and the porosity was 35%. Agent A was added to a mixing container and stirred, then agent B was added in batches to uniformly disperse the solid phase component in the liquid phase component, and then agent C was added and stirring continued to obtain a uniform and stable grouting slurry.
[0074] The grout obtained in this embodiment has a viscosity of 385 mPa·s, a working time of 32 min, and a gel time of 22 min, according to tests. The solidified body has a 3-day compressive strength of 2.8 MPa, a 7-day compressive strength of 5.4 MPa, and a 28-day compressive strength of 8.7 MPa. The curing shrinkage rate is 0.18%, and the impermeability grade is P12. Therefore, under normal temperature, conventional moisture content, and porosity soil conditions, the grout obtained in this embodiment exhibits good pumpability, suitable gel time, and high later-stage strength, enabling the formation of a low-shrinkage, high-impermeability impermeable reinforced body.
[0075] Example 2 This embodiment provides a low-temperature non-shrink grouting material, which, by weight, comprises 48 parts of agent A, 40 parts of agent B, and 12 parts of agent C. The test environment temperature was 3°C, the moisture content of the soil layer to be grouted was 28%, and the porosity was 38%. Compared with Example 1, this embodiment appropriately increases the amount of agent B to enhance the gelation reactivity and curing strength under low-temperature conditions.
[0076] The grout obtained in this embodiment has a viscosity of 420 mPa·s, a working time of 28 min, and a gel time of 18 min, according to tests. The cured body has a 3-day compressive strength of 2.2 MPa, a 7-day compressive strength of 3.5 MPa, a 28-day compressive strength of 7.1 MPa, a curing shrinkage rate of 0.15%, and an impermeability grade of P11. This demonstrates that this embodiment can still achieve relatively rapid gelation and stable curing at a low temperature of 3℃, indicating that increasing the proportion of the active solid phase component for low-temperature curing can improve the problem of slow setting and hardening at low temperatures.
[0077] Example 3 This embodiment provides a low-temperature, non-shrink grouting material, comprising 52 parts by weight of agent A, 35 parts by weight of agent B, and 13 parts by weight of agent C. The test environment temperature was 22°C, and the moisture content of the soil layer to be grouted was 32%, with a porosity of 42%. Compared with Example 1, this embodiment increases the dosage of agents A and C and decreases the dosage of agent B to meet the requirements of high moisture content and large porosity soil layers for grout flow diffusion and gel control capabilities.
[0078] The grout obtained in this embodiment has a viscosity of 340 mPa·s, a working time of 38 min, and a gel time of 28 min, according to tests. The cured body has a 3-day compressive strength of 2.5 MPa, a 7-day compressive strength of 4.8 MPa, a 28-day compressive strength of 8.2 MPa, a curing shrinkage rate of 0.20%, and an impermeability grade of P12. Therefore, under conditions of high moisture content and large porosity soil layers, the grout of this embodiment has a low viscosity and a long working time, which is conducive to the full diffusion of the grout and filling of soil pores, resulting in good compressive strength and impermeability after curing.
[0079] Example 4 This embodiment provides a low-temperature, non-shrink grouting material, comprising 49 parts by weight of agent A, 39 parts by weight of agent B, and 12 parts by weight of agent C. The test environment temperature was 10°C, and the moisture content of the soil layer to be grouted was 24%, with a porosity of 37%. This embodiment operates under conditions of relatively low ambient temperature and moderate moisture content. By maintaining a relatively balanced ratio of agents A, B, and C, the grout achieves a good balance of fluidity, gelation speed, and curing strength.
[0080] The grout obtained in this embodiment has a viscosity of 395 mPa·s, a working time of 30 min, and a gel time of 20 min, according to testing. The cured grout has a 3-day compressive strength of 2.7 MPa, a 7-day compressive strength of 5.1 MPa, and a 28-day compressive strength of 8.5 MPa. The curing shrinkage rate is 0.17%, and the impermeability grade is P12. Therefore, this embodiment can maintain stable grout workability and high curing strength at 10℃, making it suitable for conventional foundation reinforcement and waterproofing construction.
[0081] Example 5 This embodiment provides a low-temperature, non-shrink grouting material, comprising 47 parts of agent A, 41 parts of agent B, and 12 parts of agent C by weight. The test environment temperature was 0°C, the moisture content of the soil layer to be grouted was 22%, and the porosity was 34%. Compared with Example 1, this embodiment further increases the dosage of agent B, enabling the low-temperature curing active materials such as ultrafine slag powder, high-alumina cement, and calcined kaolin to provide stronger low-temperature hydration and curing capabilities under the action of the composite activating and setting-regulating components.
[0082] The grout obtained in this embodiment has a viscosity of 445 mPa·s, a working time of 25 min, and a gel time of 15 min, according to tests. The cured body has a 3-day compressive strength of 2.0 MPa, a 7-day compressive strength of 3.2 MPa, and a 28-day compressive strength of 6.8 MPa. The curing shrinkage rate is 0.14%, and the impermeability grade is P11. Therefore, even at 0℃, this embodiment can still gel and gradually form a cured body with high strength in a relatively short time, with a low curing shrinkage rate, meeting the needs of grouting and seepage prevention reinforcement construction in winter or cold regions.
[0083] Example 6 This embodiment provides a low-temperature, non-shrink grouting material, comprising 51 parts by weight of agent A, 37 parts by weight of agent B, and 12 parts by weight of agent C. The test environment temperature was 25°C, and the moisture content of the soil layer to be grouted was 18%, with a porosity of 31%. This embodiment is suitable for soil conditions with relatively high ambient temperature, low moisture content, and low porosity. By appropriately increasing the dosage of agent A, the grout maintains good fluidity and pore penetration capacity.
[0084] The grout obtained in this embodiment has a viscosity of 360 mPa·s, a working time of 35 min, and a gel time of 25 min, according to tests. The cured body has a 3-day compressive strength of 3.0 MPa, a 7-day compressive strength of 5.7 MPa, and a 28-day compressive strength of 9.0 MPa. The curing shrinkage rate is 0.19%, and the impermeability grade is P12. Therefore, this embodiment can achieve high early and late strength, while maintaining a low curing shrinkage rate and a high impermeability grade under optimal working conditions at room temperature.
[0085] Example 7 This embodiment provides a low-temperature, non-shrink grouting material, comprising 50 parts of agent A, 36 parts of agent B, and 14 parts of agent C by weight. The test environment temperature was 15°C, the moisture content of the soil layer to be grouted was 26%, and the porosity was 39%. Compared with Example 1, this embodiment appropriately increases the dosage of agent C to enhance the activation and setting effect, enabling the grout to maintain rapid gelation and stable solidification even in soil layers with slightly higher moisture content.
[0086] The grout obtained in this embodiment has a viscosity of 375 mPa·s, a working time of 27 min, and a gel time of 16 min, according to tests. The cured body has a 3-day compressive strength of 2.6 MPa, a 7-day compressive strength of 5.0 MPa, and a 28-day compressive strength of 8.3 MPa. The curing shrinkage rate is 0.16%, and the impermeability grade is P12. Therefore, under medium-temperature, high-moisture-content soil conditions, this embodiment can shorten the gel time by increasing the dosage of the composite activating and setting-regulating component, and achieve good compressive strength, low shrinkage performance, and impermeability while ensuring construction operability.
[0087] As can be seen from the above, and considering Examples 1 to 7, the low-temperature non-shrink grouting material provided by the present invention can form a stable grouting slurry in environments ranging from 0℃ to 25℃. The slurry viscosity is 340–445 mPa·s, the working time is 25–38 min, and the gel time is 15–28 min, which can meet the requirements of on-site pumping and grouting diffusion. Under normal temperature conditions, the compressive strength of the cured body is not less than 2.5 MPa after 3 days and can reach more than 8.0 MPa after 28 days. Under low-temperature conditions of 0–5℃, the compressive strength of the cured body can still reach more than 3.0 MPa after 7 days and more than 6.5 MPa after 28 days, indicating that the material of the present invention has good low-temperature curing ability. The curing shrinkage rate of each example is not higher than 0.20%, and the impermeability grade reaches P11–P12, indicating that the material of the present invention can effectively reduce the risk of curing shrinkage and microcrack formation, and improve the impermeability, density, and long-term durability of the cured body.
[0088] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A low-temperature non-shrink grouting material, characterized in that, It includes pre-prepared silica sol-based liquid phase components, low-temperature curing active solid phase components, and composite activation and solidification regulating components; by mass parts, the silica sol-based liquid phase components are 45-52 parts, the low-temperature curing active solid phase components are 35-42 parts, and the composite activation and solidification regulating components are 8-13 parts. The silica sol-based liquid phase component is a neutral, low-viscosity modified silica sol liquid phase, comprising 28-34 parts of modified silica sol, 10-15 parts of deionized water, 2.5-3.8 parts of nano-titanium dioxide dispersion, 0.8-1.5 parts of organic retarding dispersant, and 0.2-0.5 parts of environmentally friendly chelating agent; The low-temperature curing active solid phase component is a low-temperature curing active solid phase, and includes 18-22 parts of ultrafine slag powder, 7-10 parts of high-alumina cement, 5-7 parts of calcined kaolin, 2.5-4 parts of expanded microspheres, 2-3.5 parts of basalt ultrafine powder and 0.5-1.2 parts of water-soluble starch ether. The composite activated condensation regulating component is an activated regulating phase, and includes 3.5-5 parts of anhydrous sodium sulfate, 1.2-2.5 parts of trisodium citrate, 2-3.5 parts of nano-calcium carbonate, and 0.8-1.5 parts of polyethylene glycol; The silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component are mixed to form a pumpable grout with a total solid content of 38-45 wt%.
2. The low-temperature non-shrink grouting material according to claim 1, characterized in that, The modified silica sol is a neutral hydroxyl-modified silica sol; The neutral hydroxyl-modified silica sol has a particle size of 12–18 nm, a silica solid content of 32–38 wt%, a pH value of 6.8–7.5, a viscosity of 1.2–1.8 mPa·s, and a surface hydroxyl grafting rate of 12–15%.
3. The low-temperature non-shrink grouting material according to claim 1, characterized in that, The nano-titanium dioxide dispersion has a particle size of 5-8 nm, a solid content of 20-25 wt%, and a rutile crystal form. The dispersion medium of the nano-titanium dioxide dispersion is deionized water.
4. The low-temperature non-shrink grouting material according to claim 1, characterized in that, The ultrafine slag powder has a specific surface area of 480–520 m² / kg and an activity index of not less than 95%. The high-alumina cement exhibits a low-temperature hydration activity greater than 0.6 at 0℃. The particle size of the calcined kaolin is no greater than 5 μm; The particle size of the basalt ultrafine powder is no greater than 10 μm.
5. The low-temperature non-shrink grouting material according to claim 1, characterized in that, The expanded microspheres are hollow glass microspheres; The expanded microspheres have a particle size of 100–150 μm, a wall thickness of 10–15 μm, a bulk density of 0.25–0.35 g / cm³, and a volume expansion rate of 3–5%.
6. The low-temperature non-shrink grouting material according to claim 1, characterized in that, The ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component is adjusted according to the construction environment temperature, soil moisture content, and soil porosity. When the ambient temperature during construction is 5–25℃, the soil moisture content is 15–25%, and the soil porosity is 30–40%, the mass ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component is (48–52):(36–40):(10–13). When the ambient temperature during construction is 0–5℃ and the soil moisture content is not greater than 30%, the mass ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component is (46–50): (38–42): (10–13). When the soil moisture content is greater than 25% and the soil porosity is greater than 40%, the mass ratio of the silica sol-based liquid phase component, the low-temperature curing active solid phase component and the composite activated setting component is (50-54): (33-37): (11-14).
7. A method for preparing the low-temperature non-shrink grouting material according to any one of claims 1-6, characterized in that, Includes the following steps: Deionized water, modified silica sol, nano titanium dioxide dispersion, organic retarding dispersant and environmentally friendly chelating agent were mixed sequentially and filtered to obtain silica sol-based liquid phase components; After grinding and mixing ultrafine slag powder, high-alumina cement, calcined kaolin and basalt ultrafine powder, expanded microspheres and water-soluble starch ether are added and mixed. After sieving, a low-temperature solidified active solid phase component is obtained. Anhydrous sodium sulfate, trisodium citrate and nano calcium carbonate were mixed, and polyethylene glycol was added and mixed again. After sieving, a composite activated coagulation regulating component was obtained. The silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component are sealed and stored separately, and then mixed according to a preset ratio to form a grouting slurry before construction.
8. The preparation method according to claim 7, characterized in that, The modified silica sol is prepared in the following manner: Tetraethyl orthosilicate and deionized water were mixed in a molar ratio of 1:8, ammonia was added as a catalyst, and the mixture was stirred and hydrolyzed at 40°C. After filtration and concentration, the modified silica sol was obtained.
9. The preparation method according to claim 7, characterized in that, The step of separately sealing and storing the silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activated setting-regulating component, and mixing them according to a preset ratio to form the grouting slurry before construction includes: Add agent A to the mixing container and stir at low speed; add agent B to agent A in batches and stir to mix. After agent B is evenly dispersed, agent C is added and stirring is continued. After stirring is completed, a grout with a viscosity of 350-450 mPa·s, a working time of 25-40 min, and a gel time of 15-35 min is obtained.
10. A construction method using the low-temperature non-shrink grouting material according to any one of claims 1-6, characterized in that, Includes the following steps: The moisture content, porosity, particle size distribution, groundwater level, and ambient temperature of the soil layer to be grouted were determined, and the mixing ratio of silica sol-based liquid phase component, low-temperature curing active solid phase component, and composite activated setting regulator component was determined based on the test results. The silica sol-based liquid phase component, the low-temperature curing active solid phase component, and the composite activation and setting regulating component are mixed according to the mixing ratio to prepare the grouting slurry. Drill grouting holes in the area to be grouted, and lower the vibratory grouting pipe to the target grouting depth in the grouting holes; Start the grouting equipment and vibrating grouting pipe to allow the grout to enter the pores of the soil layer to be grouted under the grouting pressure and vibration. After the bottom grouting is completed, the vibratory grouting pipe is raised layer by layer according to the preset lifting height, and the grouting pressure and vibration frequency are increased layer by layer during the lifting process so that the grouting slurry can spread along soil layers of different depths. After grouting to the preset height, pressure stabilization and sealing are performed, and the grout is allowed to solidify in the soil layer to form a seepage-proof reinforced body.